Hedge fund franchises - FUNG, William (Institutional Knowledge at Singapore Management University, 2017)
Duplicate, see https://ink.library.smu.edu.sg/lkcsb_research/5964/. We investigate the growth strategies of hedge fund firms. We find that firms with successful first funds are able to launch follow-on funds that charge higher performance fees, set more onerous redemption terms, and attract greater inflows. Motivated by the aforementioned spillover effects, first funds outperform follow-on funds, after adjusting for risk. The multiple-product growth strategy hurts investors while benefiting hedge fund firms; multiple-product firms underperform single-product firms but harvest greater fee revenues. Investors respond to this growth strategy by redeeming from first funds of firms with follow-on funds that do poorly. Moreover, skilled investors allocate more capital to first than to follow-on hedge funds. Empirically, the multiple-product firm has become the dominant business model for the hedge fund industry.